(untitled) (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
Critically Endangered bird species face extinction risks compounded by genomic erosion – the progressive loss of genetic diversity through inbreeding, genetic drift, and accumulation of deleterious mutations in small remnant populations. Whole-genome sequencing now enables unprecedented resolution of genomic diversity, inbreeding coefficients, runs of homozygosity (ROH), and historical demographic trajectories in threatened taxa, providing actionable data for conservation management. This study characterised the genomic landscape of 16 Critically Endangered bird species spanning eight orders, sequencing 387 individuals at mean 18.4x genome coverage using Illumina short-read platforms. Genomic heterozygosity ranged from 0.00089 (Spix’s macaw, Cyanopsitta spixii) to 0.00412 (Bali myna, Leucopsar rothschildi) across species, with a mean of 0.00241 +- 0.00087 – substantially lower than published values for non-threatened congeners (mean 0.00634 +- 0.00142; t-test: t = 14.84, p < 0.001). Mean inbreeding coefficients (F) averaged 0.187 +- 0.064 across species, exceeding the threshold associated with inbreeding depression in birds (F > 0.125) in 13 of 16 species. Historical effective population sizes (Ne) reconstructed via pairwise sequentially Markovian coalescent (PSMC) analysis revealed that all 16 species experienced severe demographic bottlenecks, with Ne declining by 84-97% from pre-decline peaks. Genomic load analysis identified 2.4-fold more predicted deleterious variants per individual in CR species than in non-threatened relatives (p < 0.001). These findings provide a genomic evidence base for prioritising gene flow augmentation, genetic rescue, and genome banking as emergency conservation interventions for the most genomically depleted species.